A Review of Automated Reasoning and Its Applications in the 21st Century. - Ndungi, Rebeccah; Uyun , Shofwatul (AI Society & STMIK Indonesia, 2023)
This article takes a look at the progress and advancement of automated reasoning and its applications in the 21st century. Reasoning refers to the method of reaching logical conclusions. The construction of computing systems that automate this process over some knowledge bases is the focus of automatic reasoning. Automated Reasoning is frequently regarded as a subfield of machine learning. It is also studied in theoretical computer science and philosophy. Some of the applications of automated reasoning include but not limited to Tableau-style systems, Automatic Theorem Proving, Superposition and Saturation, benchmarks and Classical First-Order Logic. The development of formal led to the development of artificial intelligence, which was essential in the development of artificial intelligence for reasoning.